Analisis Kesulitan Peserta Didik Kelas IV SDN 44 Ampenan Dalam Memecahkan Soal Cerita Materi Pecahan Tahun Pelajaran 2020/2021 - Afkarina, Iza; Arjuddin; Safruddin (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
Abstrak: This study aims to determine the forms of difficulties faced by students in solving math problems in the form of stories in the fourth grade of the 44 Ampenan State Elementary School. The subjects of this study were the fourth grade elementary school students as many as 20 students. This research uses descriptive research method. Data collection techniques using tests and interviews. Students are given a test in the form of a math problem in the form of a fraction meter story. Before being used, the questions and interview sheets were first tested for validity. After obtaining research data, researchers analyzed the research data using Miles and Huberman model data analysis techniques. Based on the results of the study, obtained 3 types of difficulties faced by students in solving math problems in the form of stories. The forms of difficulty are (1) the difficulty of students in determining the steps for solving story problems, (2) the difficulty of students in converting information into mathematical sentences, and (3) difficulties in determining arithmetic operations. The difficulty of students in determining the steps for solving story problems obtains the highest percentage, which is 32.5%, the difficulty of students in converting information into mathematical sentences is 26% and the last is the difficulty in determining arithmetic operations as much as 24.5%. Keywords: difficulty solving problems, math problems in the form of stories